Spatiotemporal Dynamics of Affective and Semantic Valence Among Women - Wang, Luchun; Li, Xiying; Pi, Zhongling; Xiang, Shuoqi; Yao, Xuemei; Qi, Senqing (Frontiers in Human Neuroscience, 2021)
As an important dimension of emotional assessment, valence can refer to affective valence reflecting the emotional response or semantic valence reflecting knowledge about the nature of the stimulus. A previous study has used repeated exposure to separate these two similar cognitive processes. Here, we compared for the first time the spatiotemporal dynamics of affective and semantic valence by combining event-related potentials (ERPs) with repeated exposure. Forty-seven female participants were assigned into the feeling-focused and the semantic-focused groups and thereafter repeatedly viewed the pictures. Self-report behavioral results showed that post-test scores were significantly lower than pre-test scores in the feeling-focused group, while the differences between the two tests were not significant in the semantic-focused group. At the neural level, N2 amplitudes decreased and the early late positive potential (LPP) amplitudes increased for both groups, suggesting that participants perceived the repeated pictures more fluently and retrieved the traces of the stimulus spontaneously regardless of the valence they judged. However, the late LPP amplitudes in anterior areas and the activity of the middle frontal gyrus attenuated in the feeling-focused group, whereas this component in posterior areas and the activity of the precentral gyrus increased in the semantic-focused group. Therefore, the processes of affective and semantic valence are similar in the early stages of image perception and retrieval, while in the later stage of valence judgment, the processes of them show different brain activation patterns. Our results provide electrophysiological evidence for the differences in psychological processes when judging two modes of valence.